FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE PADA PERUSAHAAN INFRASTRUKTUR DI BEI - Dominigus, Felicia Angeline; Sudirgo, Tony (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to empirically prove the effect of financial performance, capital structure, and firm size on firm value on infrastructure companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2020. Based on the criteria that have been set, there are 16 companies from the infrastructure sector were selected as samples in this study using purposive sampling method. The analytical method used in this study is multiple linear regression using Eviews version 12. The results obtained from this study indicate that financial performance has a positive and significant effect on firm value, while capital structure has a negative and insignificant effect on firm value. Then, firm size has a negative and insignificant effect on firm value.